2010
DOI: 10.5194/acp-10-8873-2010
|View full text |Cite
|
Sign up to set email alerts
|

Response of tropical stratospheric O<sub>3</sub>, NO<sub>2</sub> and NO<sub>3</sub> to the equatorial Quasi-Biennial Oscillation and to temperature as seen from GOMOS/ENVISAT

Abstract: Abstract. The stellar occultation spectrometer GOMOS (Global Ozone Monitoring by Occultation of Stars) on ESA's Envisat satellite measures vertical profiles O 3 , NO 2 and NO 3 with a high long-term stability due to the self-calibrating nature of the technique. More than 6 years of GOMOS data from August 2002 to end 2008 have been analysed to study the inter-annual variation of O 3 , NO 2 and NO 3 in the tropics. It is shown that the QBO of the equatorial wind induces variations in the local concentration larg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 25 publications
(31 reference statements)
5
20
0
Order By: Relevance
“…The simulated maximum amplitude at around 30 hPa (~24 km) of about 10 % in relative value (anomaly divided by its climatology), from +0.6 to -0.4 ppmv in abundance range, below the phase transition is slightly smaller than observations. The amplitude of about 4 % (~0.4 ppmv) at around 10 hPa (~31 km in the model) above the phase transition is very similar to the observed values of about 5 % at 31 km (Zawodny and McCormick, 1991;Chipperfield et al, 1994;Hauchecorne et al, 2010). While the O3 amplitude below 50 hPa is small in absolute values, it is much larger in relative values (not shown due to out of scale) than that at 30 hPa, being consistent with GOMOS data (Hauchecorne et al, 2010).…”
Section: Pathway Analysis Programsupporting
confidence: 86%
See 2 more Smart Citations
“…The simulated maximum amplitude at around 30 hPa (~24 km) of about 10 % in relative value (anomaly divided by its climatology), from +0.6 to -0.4 ppmv in abundance range, below the phase transition is slightly smaller than observations. The amplitude of about 4 % (~0.4 ppmv) at around 10 hPa (~31 km in the model) above the phase transition is very similar to the observed values of about 5 % at 31 km (Zawodny and McCormick, 1991;Chipperfield et al, 1994;Hauchecorne et al, 2010). While the O3 amplitude below 50 hPa is small in absolute values, it is much larger in relative values (not shown due to out of scale) than that at 30 hPa, being consistent with GOMOS data (Hauchecorne et al, 2010).…”
Section: Pathway Analysis Programsupporting
confidence: 86%
“…The model reproduces the phase transition of the ozone QBO from dynamical to photochemical control at around 28 km (~18 hPa) in observations by SAGE II (e.g., Zawodny and McCormick, 1991;Chipperfield et al, 1994) and GOMOS (Hauchecorne et al, 2010), resulting in a dogleg-shape pattern with a vertex slightly above 20 hPa in the ozone anomaly.…”
Section: Pathway Analysis Programmentioning
confidence: 60%
See 1 more Smart Citation
“…It is possibly not the case in reality, if volcanoes, solar activity or other sporadic factors are also playing a role in the ozone budget. For instance, the influence of Quasi Biennal Oscillation (QBO) on ozone was shown to depend on altitude: Hauchecorne et al (2010) found three different regions with different influences. Also, the period of QBO is not fixed, and regression may be inaccurate.…”
Section: Ozonementioning
confidence: 99%
“…In a companion paper of this GOMOS ACP issue, Hauchecorne et al (2010) have investigated the impact of the Quasi-Biennial Oscillation (QBO) of the equatorial wind on the inter-annual variations of ozone and NO 2 . A six years period of GOMOS data from August 2002 to December 2008 recorded between 15 • S and 15 • N was analysed, first by establishing a seasonal mean, and then dividing all data by this seasonal mean.…”
Section: The Influence Of the Qbo On Tropical Stratospheric Ozone Nomentioning
confidence: 99%